Parenting Patterns for Early Childhood - Tania, Putri Muliani; Alfita, Laili (Mahesa Research Center, 2025)
Parenting can be interpreted as a model in educating, caring for, and caring for children so that they grow into independent individuals. This study aims to examine how parenting affects the development of early childhood. The research method uses the Systematic Literature Review (SLR) approach with PRISMA, which is carried out systematically by tracing related journals. The results of the study indicate that parenting has a significant influence on the formation of attitudes, traits, and emotional development of children. Parenting that is applied consistently will help children build good character and social skills. Thus, parents have an important role in shaping children's personalities from an early age through appropriate parenting, to support optimal child development in the future.